Role of Regulatory T Cells in Regulating Fetal-Maternal Immune Tolerance in Healthy Pregnancies and Reproductive Diseases - Huang, Ning; Chi, Hongbin; Qiao, Jie (Frontiers in Immunology, 2020)
Regulatory T cells (Tregs) are a specialized subset of T lymphocytes that function as suppressive immune cells and inhibit various elements of immune response in vitro and in vivo. While constraining in the number or function of Tregs can be exploited to evoke an effective anti-tumor response, sufficient expansion of Tregs is essential for successful organ transplantation and for promoting tolerance of self and foreign antigen. The immune-suppressive property of Tregs equips this T lymphocyte subpopulation with a pivotal role in the establishment and maintenance of maternal tolerance to fetal alloantigens, which is necessary for successful pregnancy. Elevation in the level of pregnancy-related hormones including estrogen, progesterone and human chorionic gonadotropin promotes the recruitment and expansion of Tregs, directly implicating these cells in the regulation of fetal-maternal immune tolerance. Current studies have provided evidence that a defect in the number or function of Tregs contributes to the etiology of several reproductive diseases, such as recurrent spontaneous abortion, endometriosis, and pre-eclampsia. In this review, we provide insight into the underlying mechanism through which Tregs contribute to pregnancy-related immune tolerance and demonstrate the association between deficiencies in Tregs and the development of reproductive diseases.